Investigating the contribution of carbon nanotubes and diesel-biodiesel blends to emission and combustion characteristics of diesel engine. (1st February 2021) - Alenezi, Raslan A.; Norkhizan, A.M.; Mamat, R.; Erdiwansyah,; Najafi, G.; Mazlan, Mohamed
Abstract: The ultimate purpose of the current research work is to trigger the effect of 50, 100 and 150 ppm multi-walled carbon nanotubes (MWCNTs) in addition to diesel-biodiesel blended fuels with a focus on the emission and combustion characteristics of diesel engine. A single-cylinder diesel engine, with 1800 rpm engine speed and 100% engine load, was used to run the experiments on all fuel blends. The results indicated a significant reduction of the carbon dioxide (CO2 ) formation as a result of increase in MWCNTs, particularly for B20 and B30 samples. Also, the results emphasized a significant reduction of nitrogen oxides (NOx) formation as fa as B20 and B40 blends were concerned. However, regarding the B10 blends, an increasing trend of NOx emissions were reported when there was an increase in MWCNTs content. Furthermore, increased in-cylinder pressure for the baseline diesel was not found to be influenced by 10% biodiesel addition and 50 ppm MWCNTs. In-cylinder pressure for B10C50 was found to follow the same behaviour as D100 baseline diesel. In addition, the highest in-cylinder pressure of 73.47 bar was attributed to the B10C150 sample, representing a value 4.64% higher than the conventional D100. It was also observed that at low MWCNTs content (50 ppm), the effect on the in-cylinder temperature was the highest. When there was maximum in-cylinder pressure, the 15°CA was determined to be the peak in-cylinder temperature for all samples. All in all, it was confirmed that the combustion characteristics and emission reductions were improved as a result of MWCNTs addition to the biodiesel-diesel blends.